THE IMPLEMENTATION OF ARCS LEARNING-MOTIVATIONAL MODEL TO ENHANCE STUDENTS’ LISTENING PROFICIENCY - Febrika dwi lestari (English Teaching and Linguistics Journal (ETLiJ), 2021)
Listening skill have a significant roles in the success of English language learning that involves the learners experiencing variety of feelings whether depression and frustration. Teaching this skill is also one of the most difficult task to do. Otherwise, motivation is one of the important things in mastering English that include listening as one of its skills. ARCS model combine both motivating and method in teaching that can be used to improve students’ proficiency in listening. This model was implemented on the second semester students of Nommensen HKBP University to find out its significance on the students’ listening skill. The quantitative analysis that used on this study showed that this model gave the significant development on the students’ proficiency on listening skill. Thus students gain more significance on the four steps of ARCS model called; attention, relevance, confidence and satisfaction that can help them to enhance their listening proficiency.